2020
DOI: 10.1038/s41598-020-77674-y
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol enhances cytotoxicity of anti-cancer drugs in human head and neck squamous cell carcinoma

Abstract: Cannabidiol (CBD) has anti-tumorigenic activity. However, the anti-cancer effect of CBD on head and neck squamous cell carcinoma (HNSCC) remains unclear. The cytotoxicity of CBD on HNSCC was analyzed using cell survival and colony-forming assays in vitro. RNA-seq was used for determining the mechanism underlying CBD-induced cell death. Xenograft mouse models were used to determine CBD’s effects in vivo. CBD treatment significantly reduced migration/invasion and viability of HNSCC cells in a dose- and time-depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(77 citation statements)
references
References 52 publications
(56 reference statements)
2
66
0
Order By: Relevance
“…Our current data suggest that novel efficacy of CBD is considered to have a modulating mechanism on decreased expression of β-catenin by testosterone or PMA. Numerous cell culture and animal studies showed antitumor effects of cannabinoids in various cancer types [ 36 , 37 ]. CBD may enhance uptake or increase the potency of certain drugs used to treat cancer suggesting that CBD might have promising efficacy for treatment for many types of diseases including alopecia and cancers [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our current data suggest that novel efficacy of CBD is considered to have a modulating mechanism on decreased expression of β-catenin by testosterone or PMA. Numerous cell culture and animal studies showed antitumor effects of cannabinoids in various cancer types [ 36 , 37 ]. CBD may enhance uptake or increase the potency of certain drugs used to treat cancer suggesting that CBD might have promising efficacy for treatment for many types of diseases including alopecia and cancers [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Some neural system cancers are presented in Table 2 . CBD inhibits cancer cell growth and migration and affects the disruption of F-actin integrity [ 82 , 83 , 84 , 85 , 86 , 87 ]. Moreover, CBD inhibits migration and invasion of endothelial cells and angiogenesis.…”
Section: Anticancer Activity Of Cannabidiol (Cbd)mentioning
confidence: 99%
“…CBD can promote CDKN1A (p21) expression in cells. Increased p21 protein expression evokes cell cycle arrest via cyclin D inhibition and the stimulation of GADD45A/B expression [ 83 ]. CBD can also induce endoplasmic reticulum (ER) stress [ 87 , 89 ], inhibiting AKT and mTOR signaling and subsequently decreasing the levels of phosphorylated mTOR and cyclin D1.…”
Section: Anticancer Activity Of Cannabidiol (Cbd)mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent evidence has demonstrated that CBD is a promising anticancer drug as it exhibits pronounced cytotoxicity against several cancer types, with a preference against T-ALL [14 -17]. In addition to its anticancer properties, CBD has demonstrated broader benefits for cancer therapy through pain relief and enhancement of the cytotoxicity of anticancer drugs such as cisplatin, 5-fluorouracil or paclitaxel, a reduction of migration and metastasis and a limitation of the adverse effects of chemotherapy as in the case of doxorubicin use [18][19][20]. The antileukemic activity of TAM has been revealed in pre-clinical trials, using leukemic cell lines and primary cells, derived from leukemic patients [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%